2012
DOI: 10.1182/blood-2012-02-408674
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming reprogramming resistance of Fanconi anemia cells

Abstract: IntroductionFanconi anemia (FA) is a recessive syndrome characterized by BM failure, congenital anomalies, and a predisposition to malignancy. 1 In vitro myeloid and erythroid colony growth of BM and peripheral blood cells from FA patients is decreased, suggesting the contribution of an intrinsic cellular defect to the BM failure. 2,3 FA cells have a defect in DNA repair that leads to spontaneous chromosomal breakage and increased sensitivity to DNA bifunctional crosslinking agents such as mitomycin C and diep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
4
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 51 publications
(72 reference statements)
7
123
4
3
Order By: Relevance
“…Because FA fibroblasts are difficult to reprogram, this study uncovered a novel role of the FA pathway in cell reprogramming. Consequently, correcting FA genes restores the reprogramming efficiency of FA fibroblasts to IPS cells [93][94][95][96][97][98]. Reprogramming induces the DDR [99] and activates the FA pathway [94], leading to P53-mediated apoptosis and low reprogramming efficiency [96].…”
Section: Novel Therapies: From Genes To Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because FA fibroblasts are difficult to reprogram, this study uncovered a novel role of the FA pathway in cell reprogramming. Consequently, correcting FA genes restores the reprogramming efficiency of FA fibroblasts to IPS cells [93][94][95][96][97][98]. Reprogramming induces the DDR [99] and activates the FA pathway [94], leading to P53-mediated apoptosis and low reprogramming efficiency [96].…”
Section: Novel Therapies: From Genes To Patientsmentioning
confidence: 99%
“…Consequently, correcting FA genes restores the reprogramming efficiency of FA fibroblasts to IPS cells [93][94][95][96][97][98]. Reprogramming induces the DDR [99] and activates the FA pathway [94], leading to P53-mediated apoptosis and low reprogramming efficiency [96]. This is partially circumvented by preventing reactive oxygen species (ROS)-mediated DNA damage [94] or by suppressing P53 during reprogramming using RNA interference [96] or human papillomavirus P53-repressing E6 protein [100].…”
Section: Novel Therapies: From Genes To Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming to discern the biochemical pathways required for the efficient and safe reprogramming of adult somatic cells into iPSCs, recent studies have shown the relevance of telomere homeostasis [2][3][4], signal transducers, and DNA repair proteins [4][5][6][7] in cell reprogramming. These results have shown that a significant DNA stress-reflected by an increased number of DNA double strand breaks (DSBs)-is produced during the reprogramming process.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these potential advantages of iPSC-based modeling, there have only been very limited numbers of iPSCbased blood disease models that have shown either the disease features or the feasibility of gene therapy (Table 2) [14,[26][27][28][29][30]. The first comprehensive proof-of-principle study to demonstrate the potential of iPSCs in any disease modeling and treatment was conducted in the mouse model N/D not determined of sickle cell disease (SCD) [31].…”
Section: Blood Disease Modeling Using Human Ipscsmentioning
confidence: 99%